Alcohol-related liver disease: Clinical practice guidelines by the Latin American Association for the Study of the Liver (ALEH) (2019)
ABSTRACT: Alcohol-related liver disease (ALD) is a major cause of advanced chronic liver disease in Latin-America, although data on prevalence is limited. Public health policies aimed at reducing the alarming prevalence of alcohol use disorder in Latin-America should be implemented. ALD comprises a clinical-pathological spectrum that ranges from steatosis, steatohepatitis to advanced forms such as alcoholic hepatitis (AH), cirrhosis and hepatocellular carcinoma. Besides genetic factors, the amount of alcohol consumption is the most important risk factor for the development of ALD. Continuous consumption of more than 3 standard drinks per day in men and more than 2 drinks per day in women increases the risk of developing liver disease. The pathogenesis of ALD is only partially understood and recent translational studies have identified novel therapeutic targets. Early forms of ALD are often missed and most clinical attention is focused on AH, which is defined as an abrupt onset of jaundice and liver-related complications. In patients with potential confounding factors, a transjugular biopsy is recommended. The standard therapy for AH (i.e. prednisolone) has not evolved in the last decades yet promising new therapies (i.e. G-CSF, N-acetylcysteine) have been recently proposed. In both patients with early and severe ALD, prolonged abstinence is the most efficient therapeutic measure to decrease long-term morbidity and mortality. A multidisciplinary team including alcohol addiction specialists is recommended to manage patients with ALD. Liver transplantation should be considered in the management of patients with end-stage ALD that do not recover despite abstinence. In selected cases, increasing number of centers are proposing early transplantation for patients with severe AH not responding to medical therapy.